Kidney disease profile and encountered problems during follow-up in Syrian refugee children: a multicenter retrospective study - YILDIZ, NURDAN (SPRINGER, 2022)
Background Children are one of the most vulnerable groups in conflict zones, especially those with chronic diseases. This study aimed to investigate kidney disease profiles and problems during follow-up in a population of Syrian refugee children residing in Turkey. Methods Syrian refugee children aged between 0 and 18 years were included in the study. Demographic data, diagnosis, particular interventions due to nephrological problems, and problems encountered during follow-up were obtained from all participating pediatric nephrology centers. Results Data from 633 children from 22 pediatric nephrology centers were included. Mean age of the children was 94.8 +/- 61.7 months and 375 were male (59%). 57.7% had parental consanguinity and 23.3% had a close relative(s) with kidney disease. The most common kidney diseases were congenital anomalies of the kidney and urinary tract (CAKUT) (31.0%), glomerular disease (19.9%), chronic kidney disease (CKD) (14.8%), and urolithiasis (10.7%). Frequent reasons for CAKUT were nonobstructive hydronephrosis (23.0%), vesico-ureteral reflux (18.4%), and neurogenic bladder (15.8%). The most common etiology of glomerular diseases was nephrotic syndrome (69%). Ninety-four children had CKD, and 58 children were on chronic dialysis. Six children had kidney transplantation. Surgical intervention was performed on 111 patients. The language barrier, lack of medical records, and frequent disruptions in periodic follow-ups were the main problems noted. Conclusions CAKUT, glomerular disease, and CKD were highly prevalent in Syrian refugee children. Knowing the frequency of chronic diseases and the problems encountered in refugees would facilitate better treatment options and preventive measures.
Keywords: Children; Conflict zones; Kidney disease profile; Syrian refugees; NEPHROTIC SYNDROME; RENAL-DISEASES; CHILDHOOD; HEALTH; UROLITHIASIS; SPECTRUM